Changes in femoral anteversion after intramedullary nailing for pediatric femoral shaft fracture: a multicenter study - Min, Jae Jung; Kwon, Soon Sun; Youn, Kibeom; Kim, Daehyun; Sung, Ki Hyuk; Park, Moon Seok (BMC Musculoskeletal Disorders, 2024)
Background: The rotational change after using a flexible intramedullary (IM) nail for femoral shaft fractures has been a concern for many surgeons. Recently, a statistical shape model (SSM) was developed for the three-dimensional reconstruction of the femur from two-dimensional plain radiographs. In this study, we measured postoperative femoral anteversion (FAV) in patients diagnosed with femoral shaft fractures who were treated with flexible IM nails and investigated age-related changes in FAV using the SSM. Methods: This study used radiographic data collected from six regional tertiary centers specializing in pediatric trauma in South Korea. Patients diagnosed with femoral shaft fractures between September 2002 and June 2020 and patients aged < 18 years with at least two anteroposterior (AP) and lateral (LAT) femur plain radiographs obtained at least three months apart were included. A linear mixed model (LMM) was used for statistical analysis. Results: Overall, 72 patients were included in the study. The average patient age was 7.6 years and the average follow-up duration was 6.8 years. The average FAV of immediate postoperative images was 27.5 ± 11.5°. Out of 72 patients, 52 patients (72.2%) showed immediate postoperative FAV greater than 20°. The average FAV in patients with initial FAV > 20° was 32.74°, and the LMM showed that FAV decreased by 2.5° (p = 0.0001) with each 1-year increase from the time of initial trauma. Conclusions: This study explored changes in FAV after femoral shaft fracture using a newly developed technology that allows 3D reconstruction from uncalibrated 2D images. There was a pattern of change on the rotation of the femur after initial fixation, with a 2.5° decrease of FAV per year.
Keywords: Adolescent; Bone Anteversion; Bone Nails; Child; Child, Preschool; Female; Femoral Fractures; Femur; Follow-Up Studies; Fracture Fixation, Intramedullary; Humans; Imaging, Three-Dimensional; Male; Republic of Korea; Retrospective Studies; Treatment Outcome; 3D reconstruction; Pediatric femoral shaft fracture; Postoperative femoral anteversion; Uncalibrated 2D radiographs